Minat Beli Pelanggan Ditinjau Dari Aspek Harga Pada UD. Tunas Baru Kecamatan Bandar Hulu - Suhartini Suhartini; Debi Eka Putri; Vivi Candra (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The purpose of this study was to determine the price picture and customer buying interest at UD. Tunas Baru District Bandar Huluan. Next to determine the effect of prices on customer buying interest at UD. Tunas Baru District Bandar Huluan. The type of data used is qualitative and quantitative data and data sources are derived from primary data and secondary data. Research data were collected by conducting interviews, documentation and distributing questionnaires. Data analysis includes qualitative data analysis and quantitative analysis. The results of the study can be concluded from the total respondents' answers about prices with the dimensions of price affordability, discounted prices, and payment methods to obtain good answer criteria. Then from the total respondents' answers regarding buying interest got high answer criteria. Furthermore, to test the hypothesis it is concluded that there is a positive influence between price on customer buying interest.